SISTEM PEMESANAN MAKANAN MENGGUNAKAN MIKROKONTROLER ATMEGA8535 - Wilis Kaswidjanti; Dessyanto Boedi Prasetyo; Alamsyah Alamsyah (Telematika, 2010)
Some restaurants are to develop the concept by placing the gazebo-gazebo that were located far apart. With a large area and a place to eat with the amount that more and more the restaurant must provide the waitresses in considerable amounts. Often when the waiter is still busy serving the other guests, then there will be visitors restaurants that can not be served well. In addition, the number of waiters that too many would economically burden the employers because it would result in expenditure will be even greater. Then it can be developed an information system involving hardware and software to apply the reservation system that can be done from the tables or places to eat at a restaurant. Systems built using hardware and software. The hardware is built by using the AVR microcontroller device comprising an IC (Integrated Circuit) which is supported by the power supply, as well as some passive and active components. Software on a microcontroller using C language development tool using CodeVision of AVR. While the computer software using Visual Basic 6.0 programming language. Food ordering system that created it can improve services for consumers in terms of booking. Buyers can make a reservation at the dinner table without going through the waitress who had approached the table and write whatever menu you want to order. Additional bookings can also be done through the table without leaving the place or the waiter.